The first-order theory of the computably enumerable equivalence relations in the uncountable setting. (22nd July 2021) - Andrews, Uri; Lempp, Steffen; Mustafa, Manat; Schweber, Noah D
Abstract: We generalize the analysis of Andrews, Schweber and Sorbi of the first-order theory of the partial order of degrees of c.e. equivalence relations to higher computability theory, specifically to the setting of a regular cardinal.